The no-nonsense real estate investor’s kit : - Lucier, Thomas J. (John Wiley & Sons, 2006)
n The No-Nonsense Real Estate Investor’s Kit, noted author and real estate expert, Thomas J. Lucier provides detailed information, step-by-step instructions and practical advice for both beginning and experienced investors, who want to join the ranks of America's real estate millionaires!